Tuning the near infrared II emitting wavelength of small molecule dyes by single atom alteration. Issue 4 (10th December 2019) - Qian, Kun; Qu, Chunrong; Ma, Xiangyu; Chen, Hao; Kandawa-Schulz, Martha; Song, Wei; Miao, Weimin; Wang, Yihong; Cheng, Zhen
Abstract : Replacing donors' S with O and Se will red shift NIR-II dyes' fluorescence emission and offer good clarity/brightness for imaging. Abstract : A series of small molecule dyes demonstrate the feasibility of manipulating Near Infrared II emission by simply altering the donors' heteroatoms, which involved both electronegativity and intramolecular steric effects. Furthermore, these dyes show high resolution and stability for in vivo imaging after being complexed with human serum albumin.